Persis: Pergerakan Dakwah di Kota Medan Tahun 2010-2015 - Suryadi Nasution (JUSPI (Jurnal Sejarah Peradaban Islam), 2020)
This research aims to identify the  Islamic unity movement  in the North Sumatera in the field  education, preaching, culture, and society environment. The research approach of this study uses case study to describe the development of Islamic Unity in the north sumatera.  Techniques for collecting data uses  observation, interview, and documentation by gathering the observation result, reduction, data description and result discussion. Commonly the Islamic Unity Movement is divided into two part, first, preaching (Da’wah) movement through the distribution of Islamic Unity’s bulletins in once a fortnight. Second, the establishment of zakat center community that serving distribution of  zakat community and giving scholarship in 15% from zakat, infaq and shadaqah’s income.